Construction of optimal portfolio Simple Sharpe Portfolio Optimization model / Wan Madzlifah Mohd. Yusoff - Mohd. Yusoff, Wan Madzlifah (1995)
The objective of this study is to construct the optimal portfolio by utilising Simple Sharpe Portfolio Optimization Model. In this study samples are taken from construction sector listed at KLSE. There are 12 companies being evaluated. Optimal portfolio is determined by looking at the cutoff rate point and the excess return to beta value. Those securities with excess return to beta value that is above the cutoff rate point C* are under the optimal portfolio. From this analysis we 'noticed that there are 9 companies under the optimal portfolio. The companies are YTL, Sg. Way, Siah Bro., UEM, Promet, Renong, IJM, PJ Dev. And Gen. Corp. These companies provide an excess return to beta value higer than C'. This portfolio gives a high return and a low standard deviation on portfolio. In other words these are the companies that will maximised the shareholders' wealth. Simple Sharpe Portfolio Optimization Model helps the manager as well as the investors to maximise thier return.